The effectiveness of crushed onion compresses in reducing baby's body temperature 1-6 months after DPT immunization - Susilawati, Susilawati; Skania, Pratiwi Cahya; Fairuza, Filda; Ramdani, Tiara Putri (Institute of Computer Science (IOCS), 2024)
Fever is a common symptom of illness in Indonesia, including in children. One effort to reduce fever with non-pharmacological therapy is compressed crushed shallots (Allium Cepa L) which contain flavonoids which have the benefit of protecting cell structure, anti-inflammatory, increasing the effectiveness of vitamin C, as a natural antibiotic. The aim of this research is to determine the effect of giving crushed red onion (Allium Cepa L) compresses on reducing baby's body temperature 1-6 months after immunization at TPMB Bd Fenty Sumara, Serang City. This research uses the quantitative Quasy Experiment method with a one group pretest – posttest design. The sampling technique for this research was total sampling of 30 respondents. The time of the research was April-May 2024. The results showed that compressing crushed onions on babies aged 1-6 months who had fever showed an average decrease of 0.65oC during 50-60 minutes of compression. The average before the compress could be seen was 38. 25oC and the average after compression is 37.60oC. Test Shapiro-Wilk statistics obtained a P value = 0.000 < 0.05. The conclusion from this research is that there is an effect of crushed red onion (Allium Cepa L) compress on reducing the baby's body temperature 1-6 months after DPT immunization.